Development of a set of process and structure indicators for palliative care: the Europall project - Woitha Kathrin; Van Beek Karen; Ahmed Nisar; Hasselaar Jeroen; Mollard Jean-Marc; Colombet Isabelle; Radbruch Lukas; Vissers Kris; Engels Yvonne (BMC, 2012)
Abstract Background By measuring the quality of the organisation of palliative care with process and structure quality indicators (QIs), patients, caregivers and policy makers are able to monitor to what extent recommendations are met, like those of the council of the WHO on palliative care and guidelines. This will support the implementation of public programmes, and will enable comparisons between organisations or countries. Methods As no European set of indicators for the organisation of palliative care existed, such a set of QIs was developed. An update of a previous systematic review was made and extended with more databases and grey literature. In two project meetings with practitioners and experts in palliative care the development process of a QI set was finalised and the QIs were categorized in a framework, covering the recommendations of the Council of Europe. Results The searches resulted in 151 structure and process indicators, which were discussed in steering group meetings. Of those QIs, 110 were eligible for the final framework. Conclusions We developed the first set of QIs for the organisation of palliative care. This article is the first step in a multi step project to identify, validate and pilot QIs.